2019
DOI: 10.1021/acs.biochem.9b00121
|View full text |Cite
|
Sign up to set email alerts
|

The Metastasis Suppressor Protein Nme1 Is a Concentration-Dependent Modulator of Ca2+/Calmodulin-Dependent Protein Kinase II

Abstract: Nucleoside diphosphate kinases (Nmes/NDPKs) have been implicated in a multitude of cellular processes including an important role in metastasis suppression and several enzymatic activities have been assigned to the Nme family. Nevertheless, for many of these processes, it has not been possible to establish a strong connection between Nme enzymatic activity and the relevant biological function. We hypothesized that, in addition to its known enzymatic functions, members of the Nme family might also regulate sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A simultaneous study revealed that NME1 interacts directly with the calcium-calmodulin-dependent kinase II (CAMKII). However, the H118 catalytic site mutant was as effective as the WT form of the enzyme, implying that CAMKII regulation does not involve its phosphotransfer activity [118]. Moreover, human recombinant NME1 H118F and P96S mutants were unable to phosphorylate KSR, and in transfected HEK293T cells, the P96S mutant failed to suppress unlike WT NME1, suggesting that NME1 acts as a protein kinase transferring its histidine phosphate to a serine in the KSR pathway [54].…”
Section: Nme Protein Histidine Kinase Functions As Revealed By Mutagementioning
confidence: 96%
“…A simultaneous study revealed that NME1 interacts directly with the calcium-calmodulin-dependent kinase II (CAMKII). However, the H118 catalytic site mutant was as effective as the WT form of the enzyme, implying that CAMKII regulation does not involve its phosphotransfer activity [118]. Moreover, human recombinant NME1 H118F and P96S mutants were unable to phosphorylate KSR, and in transfected HEK293T cells, the P96S mutant failed to suppress unlike WT NME1, suggesting that NME1 acts as a protein kinase transferring its histidine phosphate to a serine in the KSR pathway [54].…”
Section: Nme Protein Histidine Kinase Functions As Revealed By Mutagementioning
confidence: 96%